Socio-Demographic Profile of Psychoactive Substance Users Attending A Tertiary Care Centre - Muhammad Muslim Khan, Rizwan Farooq, Muntazir Mehdi, Usman Amin Hotiana, Asifa Afzal, Sabika Hussain (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: The goal of this analysis is to determine the proportion of psychoactive substance disorder and socio-demographic profile of Psychoactive Substance Users. Study Design: A descriptive study. Place and Duration: In the Psychiatry and Behavioral Sciences department PGMI/AMC/LGH Lahore, Pakistan and Mardan Medical Complex for six months duration from October 2021 to March 2022. Methods: A total of 120 subjects with psychoactive substance use disorder (conferring to the ICD-10 criteria) were recruited after attaining their written informed consent. In the course of the study, all patients with substance use disorders were interviewed through partially structured addiction questionnaire. Data was analyzed with SPSS version 21.0 using inferential and descriptive statistics. Results: Out of the 120 subjects, 100 were men and 20 were women. The adults and adolescents were the main groups indulging in the consumption of psychoactive substances. Most of the subjects, 45%, started substance abuse at 16-20 years of age. Of the remaining 18.3%, started substance abuse at 26 years old and older, 24.2% started at the age of 21-25 years, and 12.5% started at the age of 13-15 years. It was found that 50% were in the recovery process. The relapse rate was 33.3%, 12.5% were not in contact, 2.5% died, and 1.7% were in prison. Opioid was the psychoactive substance preferred by 66.7% of the young population. The most common opioid was brown sugar; 13.3% prefer cannabis, 2.5% prefer tablets, 4.2% prefer injectable use and 0.83% prefer volatile usage of substances. Conclusion: The main consumers of psychoactive substances were the adults and adolescents and majority start using it at a younger age. Psychoactive substance abuse is a serious problem effecting young people, which is a sensitive group. So, special consideration should be paid to psychoeducation about psychoactive substances prior to adolescent. Keywords: Psychoactive substance, Sociodemographic profile.